Colorimetric Detection Of Heavy Metal Ions Using Green Synthesised Silver Nanoparticles From Curcuma Xanthorrhiza Extract - Teh, Yoong Sin (Universiti Sains Malaysia, 2022)
Curcuma xanthorrhiza also known as temulawak is a medicinal herb which can be found widely in Southeast Asia. C. xanthorrhiza is well-known because of its distinct bioactive and phytochemical compound. In this research, the bioactive compound of C. xanthorrhiza was used to capture and reduce silver ions into silver nanoparticles (AgNPs). Effect of pH on green synthesis of AgNPs was studied under optimal condition of 8 wt% rhizome extract concentration, 1:5 rhizome extract to silver nitrate (AgNO3) solution ratio and 72 hours incubation time as conducted by previous work. The effect of pH from 5 to 11 was studied and the highest absorbance intensity peak recorded was at pH 11. The morphology of the synthesised AgNPs is spherical in overall, and the average particle size synthesised at this pH is 218.245±0.123 nm. The recorded silver content using EDX analysis was 76 %. This further confirmed silver ions were reduced to AgNPs. The AgNPs biosynthesised using the optimum parameters were used for colorimetric detection of 1 mM of heavy metal ions (Mn2+, Ni2+, Zn2+, Co2+, Fe2+, Fe3+, Al3+, Cr2+, Cd2+, Pb2+, Hg2+, and Cu2+). The AgNPs able to detect Hg2+ ion with a significant decolorization from brown to colorless observed using the naked eye. The absorbance peak at wavelength 410 nm had disappeared, indicating reduction of AgNPs. Sensitivity analysis was performed to determine the limit of detection (LOD) of the detected heavy metal ions. The LOD for Hg2+ ion is 0.342 mM. Conversely, AgNPs would also be able to detect Fe2+, Fe3+, Al3+ ions, but with an increase of absorbance peak. The color changed from brown to dark brown and yellow, respectively. The LOD for Fe2+, Fe3+, Al3+ ions are 0.431 mM, 0.688 mM, and 0.847 mM, respectively.